Opioid-related genetic polymorphisms do not influence postoperative opioid requirement: A prospective observational study. Issue 7 (July 2018) - Aubrun, Frédéric; Zahr, Noël; Langeron, Olivier; Boccheciampe, Nicolas; Cozic, Nathalie; Belin, Lisa; Hulot, Jean-Sebastien; Khiami, Frederic; Riou, Bruno
Abstract : BACKGROUND: Among the various factors that may influence the pharmacological response to opioids, genetic polymorphisms [single nucleotide polymorphisms (SNP)] have generated some interest. OBJECTIVES: To examine the influence on morphine dose requirements and adverse events in the postoperative period of four SNP [opioid receptor mu1 (OPRM1), ATP-binding cassette subfamily B, member 1 (ABCB1) ex-21 and ex-26, catechol-o-methyltransferase (COMT)] in candidate genes involved in morphine pharmacodynamics and pharmacokinetics. DESIGN: A single centre prospective study. SETTING: University Hospital, Paris, France, from 2 January 2007 to 15 November 2011. PATIENTS: A total of 438 white adults scheduled for major orthopaedic surgery (spine, hip and knee) under general anaesthesia. The main exclusion criteria were receiving opioids for chronic pain, nonopioid drugs within 2 days prior to surgery, pregnancy, renal insufficiency, sleep apnoea obstruction syndrome, morbid obesity, severe hepatic impairment, cognitive dysfunction. INTERVENTIONS: Assays of plasma concentrations of morphine and metabolites (morphine 3-glucuronide and morphine 6-glucuronide) were performed and common polymorphisms in four candidate genes [ OPRM1 A118G rs1799971; P-glycoprotein ( ABCB1 ) T3435C (rs1045642) and G2677T/A (rs2032582); COMT Val 158 Met (rs4680)] were analysed. Morphine was titrated by staff in the postanaesthesia care unit (PACU) and in the ward patient-controlled intravenous analgesia was used for 24 h. MAIN OUTCOME MEASURES: The dose of morphine required to achieve pain relief and the influence of SNP in genes involved in morphine pharmacodynamics and kinetics on morphine dose requirements. Secondary endpoints were the concentrations of morphine, morphine 6-glucuronide and morphine 3-gluguronide, the proportion of patients requiring a rescue analgesic and the proportion of morphine-related adverse events. RESULTS: A total of 404 patients completed the study to final analysis. The mean ± SD morphine dose to achieve pain relief was 15.8 ± 8.8 mg in the PACU and 22.7 ± 18.6 mg during patient-controlled intravenous administration. Morphine-related adverse events were observed in 37%. There was no relationship between any genetic polymorphisms and morphine dose, morphine 3-gluguronide and morphine 6-glucuronide concentration, morphine-related adverse events or pain level. In the PACU only, P-glycoprotein polymorphisms (ex-21; ex-26) were significantly associated with morphine concentration but the prediction of the model was poor ( R 2  = 0.04) CONCLUSION: No major relationship has been demonstrated between SNP of OPRM1, ABCB1, COMT and morphine requirement, pain level or adverse effects in the postoperative period. TRIAL REGISTRATION: NCT00822549 (www.clinicaltrials.gov ). Abstract : Supplemental Digital Content is available in the text